The Cambridge economic history of the modern world (Cambridge, United Kingdom ; New York, NY)
2 cilt (1. c. xvi, 496 sayfa ; 2. c. xv, 566 sayfa)
Keywords: “The first volume of The Cambridge Economic History of the Modern World traces the emergence of modern economic growth in eighteenth century Britain and its spread across the globe. Focusing on the period from 1700 to 1870, a team of leading experts in economic history offer a series of regional studies from around the world, as well as thematic analyses of key factors governing the differential outcomes in different parts of the global economy. Topics covered include population and human development, capital and technology, geography and institutions, living standards and inequality, international flows of trade and labour, the international monetary system, and war and empire“ -- “The second volume of The Cambridge Economic History of the Modern World explores the development of modern economic growth from 1870 to the present. Leading experts in economic history offer a series of regional studies from around the world, as well as thematic analyses of key factors governing the differential outcomes in different parts of the global economy. Topics covered include human capital, capital and technology, geography and institutions, living standards and inequality, trade and immigration, international finance, and warfare and empire“ --